ANALISIS KUALITAS REPAIR WELDING CAST WHEEL ALUMINIUM MENGGUNAKAN METODE PENGELASAN OKSI-ASETILIN DENGAN PERLAKUAN PREHEATING DAN POST WELD HEAT TREATMENT - Aftoni Heri Septian Pamungkas; Budi Harjanto; Indah Widiastuti (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The aims of this research are to find out chemical composition, micro structure, the hardness level, and the strength impact of raw material and after welding using preheating and post weld heat treatment on cast wheel aluminum. Those data were analyzed using comparative descriptive method. The equipments used for measuring the chemical composition, microstructure, the hardness level, and the strength impact are as following: Spectrometer Metal Scan, Olympus Metallurgy Microscope, Vikers Hardness Tester and Charpy Tester. Based on the experiment results, it can be concluded that the chemical composition of the main constituent of cast wheel aluminum is 7,41% Si, which can be categorized in the aluminum alloy AA4343 series. The experiment results showed a decrease in the extent of the microstructure of primary Si phase after welding. Si primary phase were spread well around the surface of 12Î±"> -Al but the result Si after oxy-acetylene welding process with preheating and PWHT indicates that the primary Si phase is reducing so that the α-Al phase is dominating. The hardness level on the welding result decreased from raw material amounted to 103.381 kgf/mm2 be 40.112 kgf/mm2 in the welding area and 44.378 kgf/mm2 in area Heat Affected Zone (HAZ). The strength impact number on welding area showed a slight increase from the raw material areas of 0.055 joules/mm2to the welding of 0.058 joule/mm2.